The Effect of Learning Motivation, Learning Discipline, and Learning Style on Academic Performance of Students Faculty of Economics, Jakarta State University - Putri Nur Lathipah Sastra Praja; Dr. Osly Usman, M.Bus Syst (Asosiasi Transformasi Digital Dan Bisnis Indonesia, 2025)
This study aims to determine whether learning motivation, learning discipline, and learning style have an effect on the academic performance of students at the Faculty of Economics, Jakarta State University. This study employs a quantitative descriptive method with 109 students from the Faculty of Economics at the Jakarta State University. The data were analyzed using the Smart PLS 3.3.7 application and the Structural Equation Modelling (SEM) technique. Based on the study's findings, the following can be concluded: 1) Learning Motivation has a positive and statistically significant effect on Learning Style, as indicated by the t statistic of 4,533 > 1,983. The t statistic of 0.678 1.94 indicates that Learning Motivation does not have a positive and statistically significant effect on Academic Performance. 3) Based on the t statistic, Learning Discipline has a positive and significant effect on Learning Style. The t statistic of 2,607 > 1,980 indicates that Learning Discipline has a positive and statistically significant impact on Academic Performance. 5) Based on the t statistic 1.714 1.983, Learning Style has no positive and significant effect on Academic Performance. 6) Based on t-statistics, learning motivation and Learning Style have no positive and significant effect on Academic Performance. 7) Based on the t statistic 1.714 > 1.983, Learning Discipline and Learning Style have no positive and significant effect on Academic Performance.